THE URGENCY OF THE ISLAMIC EDUCATION IN DRUG PREVENTION FOR THE YOUNGER GENERATION ISLAM - Hayatsyah, Hayatsyah; Tafsir, Ahmad; Syafrin, Nirwan (Tawazun: Jurnal Pendidikan Islam, 2018)
New currents of globalization and information, scientific advancement and technology, the economic crisis, the hight number of povety, social inequality, the more relegious in obedience wear off and difficult it is to get a job that generates, as the cause a trigger crime amid public life. One of the biggest crime at this time according to the goverment of Indonesia is drug abuse. Drugs already spread throughout all walks of life, it is not impossible including the younger generation Islam this happens not only in large cities but already penetraled and spread to the corners of the village. Therefore the drug threat and became the enemy of the nation and the country even religion and can break the chain of a generation and to produce a generation of weak physical and phychic in a national and international scale. The above fact should immediately in response appropriately and urgent objective to prevent and save the younger generation from the dangers of drugs by all components. So the above facts immediately and response to urgent and appropriately and must prevent by the rest of the elements, one of them is with the educative role of islamic learning including i.e the value in the real value of islamic education to vocational education and interalize the value of islamic values into the segmentation of human life. Bacause it’s very urgent drug hazard prevention is for the younger generation of is time trought islamic education as part of the national education system. Keywords : The younger generation Islam, Drugs, Islam Education.